ICBTBYOFAUNAL DIVERSITY OF GREAT NICOBAR ISLAND, BAY OF BENGAL - Rajaram, R.; Srinivasan, M.; Khan, S. Ajmal; Kannan, L. (Journal of Indian Fisheries Association, 2015)
Ichthyofauna was studied in the inshore waters around the Great Nicobar Island to assess the extent of biodiversity of fishery resources in the Great Nicobar watersÂ· by using various gears and crafts. During the present study, 258 species of fin fishes belonging to 141 genera, 84 families and 19 orders were recorded. Among these, Perciformes topped the list with 4 7 families, 84 genera and 169 species followed by Clupeiformes, Angulliformes, Tetrodoniformes, Cyprinodontiformes, Scorpaeniformes, Rajiformes, Elopiformes, Pleuronectiformes, Syluriformes, Laminiformes, Bercyformes, Aelopiformes, Syngathiformes and Gonorhychiformes which includes the medicinally important and ornamentally valuable species. Keywords: Ichthyofauna, diversity, Nicobar Island